Somatotype profile of South American swimmers - Mazza, J. C.; Cosolito, P.; Alarcon, N.; Galasso, C.; Bermudez, C.; Gribaudo, G.; Ferretti, J. L. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
Somatotype analysis was applied to 292 South American swimmers to compare a general and multinational sample (SAS), with South American Championship Finalist Swimmers (SACHS). Additionally, the somatotype of the SACHS group was compared and evaluated during the Mexico (1968) and Montreal (1976) Summer Olympic Games. The SAS group (149 males and 88 females) and SACHS group (29 males and 27 females) were measured for somatotype (Heath-Carter) to determine Endomorphy (En), Mesomorphy (Me) and Ectomorphy (Ec) components. The SACHS males were significantly older, heavier and taller than the SAS group (P < 0.01); SACHS somatotype components were 2.4-4.7-3.1, while SAS group registered 2. 7-4.8-2.9 (significant difference, P < 0.05 - was found only for En). The SACHS females were older (P < 0.01) than SAS, with no difference in weight and height. The SACHS somatotype components were 3.1-3.8-2.9, and values for SAS were 3.9-4.0-2.7. The SAS group had the higher En component (P < 0.01). Analysis of both groups according to styles revealed differences (P < 0.05) only in the En among free-stylers: SAS (both males and females) had higher En value than the SACHS group. No difference was obtained between SACHS and both Olympic samples (for males and females) for age, weight, height, En, Me, and Ec components. According to these data, it is concluded that: (a) Fewer En components for SACHS groups (both males and females) compared with SAS reflects a lower proportion of fat mass and, consequently lower En/Me ratio. (b) The similarity in somatotype components between SACHS groups and Mexico 1968 and Montreal 1976 samples (for both males and females) would suggest that there are defined somatotype profiles related to high-level performance in swimming.